2013
DOI: 10.1115/1.4024836
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Excimer Laser Cleaning of Film and Particle Contaminants

Abstract: Laser cleaning is a promising surface preparation technique for applications in high value manufacturing industries. However, understanding the effects of laser processing parameters on various types of contaminants and substrates, is vital to achieve the required cleaning efficacy and quality. In this paper, a two-dimensional transient numerical simulation was carried out to study the material ablation characteristics and substrate thermal effects in laser cleaning of aerospace alloys. Element birth and death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…First, our method considers the initial corrosion state of the metal surface quantitatively. Although some research studies mentioned the initial corrosion issue [40][41][42], more of them [43,44] still did not consider the initial corrosion state problem when performing their research studies. Clearly, our research has indicated the initial corrosion will affect the cleaning effect to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…First, our method considers the initial corrosion state of the metal surface quantitatively. Although some research studies mentioned the initial corrosion issue [40][41][42], more of them [43,44] still did not consider the initial corrosion state problem when performing their research studies. Clearly, our research has indicated the initial corrosion will affect the cleaning effect to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…传统的清洗方法包括喷砂喷丸清洗 [6] 、 化学清洗 [7] 、超声波清洗 [8] 、高压水射流清洗 [9] . 这些 人 [10] 数值模拟了准分子激光清洗膜与颗粒的温度场, 并通过实验进行验证激光清洗过程中的机制, 经分析 模拟结果与清洗实验结果一致. Sinha [11] 建立二维热模 型脉冲激光烧蚀理论模型, 通过实验验证模型的正确 性, 同时烧蚀速率没有随激光强度的增加而突然增加, 表明物质的喷射主要是通过正常沸腾机制, 通过模拟 获得合理激光清洗工艺参数, 可以降低材料表面的损 伤. Zhou等人 [12] 通过模拟可知只要选择适当的激光参 数和加工参数, 激光能有效地去除污物.…”
Section: 引言unclassified
“…R and h represent interface thermal resistance and convection heat transfer coefficient, respectively. Besides, model assumed that the densities of the coating and substrate kept a constant, and material properties were isotropic, as well the laser irradiation heating was treated as a surface heat source [20] . The thermal conductivity and heat capacity of material were measured in this work, while h = 10 W/(m 2 •K) and R = 1×10 -3 m 2 •K/W according to the Ref.…”
Section: Finite Element Modelingmentioning
confidence: 99%